Properties of integrals which have the type of derivatives of volume potentials for one ultraparabolic arbitrary order equation - Dron', V.S.; Ivasyshen, S.D.; Medyns'kyi, I.P. (Carpathian Mathematical Publications, 2019)
In weighted Hölder spaces it is studied the smoothness of integrals, which have the structure and properties of derivatives of volume potentials which generated by fundamental solutions of the Cauchy problem for one ultraparabolic arbitrary order equation of the Kolmogorov type. The coefficients in this equation depend only on the time variable. Special distances and norms are used for constructing of the weighted Hölder spaces. The results of the paper can be used for establishing of the correct solvability of the Cauchy problem and estimates of solutions of the given non-homogeneous equation in corresponding weighted Hölder spaces.